Interfaith Marriage: Perspective of Islamic Law and Positive Law - Ahmad Senang (ISNU Sumatera Utara, 2024)
Interfaith marriage is one of the complex legal issues in Indonesia, especially when examined from the perspective of Islamic law and positive law. In Islamic law, marriage has a sacred value that must be in accordance with the principles of sharia, where the prohibition of marriage between Muslims and non-Muslims is emphasized in the Qur'an and Hadith. Meanwhile, Indonesian positive law regulates marriage in Law Number 1 of 1974 which emphasizes that marriage is considered valid if it is carried out according to the religious law and beliefs of each couple. This creates ambiguity in the regulation of interfaith marriage because there are differences in the interpretation and implementation of applicable laws. This study aims to analyze interfaith marriage from the perspective of Islamic law and positive law, identify the differences and similarities between the two, and explore legal solutions that can be applied in the Indonesian legal system. The method used in this study is normative juridical with a qualitative approach, which focuses on doctrinal analysis of laws and regulations, Islamic legal literature, and relevant court decisions. The results of the study show that Islamic law strictly prohibits interfaith marriage for Muslims, except under certain conditions regulated in certain interpretations. Meanwhile, positive law in Indonesia does not explicitly prohibit, but also does not provide a clear mechanism for interfaith marriage. The conclusion of this study is that the inconsistency between Islamic law and positive law in regulating interfaith marriage causes legal uncertainty in society, so that a firmer policy and legal harmonization are needed to provide legal certainty for interfaith couples in Indonesia.